2015
DOI: 10.15561/20755279.2015.0603
|View full text |Cite
|
Sign up to set email alerts
|

Physical culture in life of Eastern-European region students: modern state and prospects of development

Abstract: Abstract. Purpose: analysis of researches on physical culture problems among students in countries of Easter-European region (2013. Material: As sources of information we chose data base of Russia, Poland and Ukraine. Besides, we used sites of the most known journals of Easter-European region. When choosing journals we based on rating of Russia (RISC), Poland (Index Copernicus) and Ukraine (bibliometryka of Ukrainian science) data bases. Results: thematic focus of researches on different physical education, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 191 publications
1
7
0
Order By: Relevance
“…At the same time in literature there are data about use of individualized physical education of students [31]. Scientists found that boy-students' physical activity level is higher than the same of girl-students [12]. Therefore, physical education programs, considering students' main demands will be wanted [37].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time in literature there are data about use of individualized physical education of students [31]. Scientists found that boy-students' physical activity level is higher than the same of girl-students [12]. Therefore, physical education programs, considering students' main demands will be wanted [37].…”
Section: Introductionmentioning
confidence: 99%
“…Searching of ways to improve students' health, development of some kinds of sports, creation of favorable conditions for formation of youth's positive attitude to healthy life style, training of professional-applied skills of future specialists and other can be considered to be the main purpose of such researches [27].…”
Section: Resultsmentioning
confidence: 99%
“…Sports education will help to increase positive effects such as the growth of students' achievement directly in training activities and their commitment to a high level of physical activity (Trudeau, & Shephard, 2008). Moreover, the scientists emphasize the need for speedy introduction of changes in the current educational programs related to the increase in the overall level of the culture of health both for the students and university professors and for the formation of persistent beliefs about the need for a healthy lifestyle and maintaining a high level of motor activity (Iermakov, Cieślicka, & Muszkieta, 2015;Bolotin, & Bakayev, 2015). There are many experts who recommend to increase the amount of physical activity of the modern students.…”
Section: Introductionmentioning
confidence: 99%